KARAKTERISTIK IMAGO Sitophilus oryzae dan S. zeamais PADA BERAS DAN JAGUNG PIPILAN (CHARACTERICS OF IMAGO Sitophilus oryzae AND S. zeamais ON RACE AND CORN) - Paut Gwijangge; Jusuf Manueke; Guntur S.J. Manengkey (COCOS, 2017)
ABSTRACTThis study aims to determine the differences of imago characteristics of S. oryzae and S. zeamais onrice and corn. This research used descriptive observational method by identifying the externalmorphology and describe all the observed parts. Morphological characters were observed byobserving the external morphological features of insects including differences of body size, bodycolor, antenna, rostrum, and other morphological features. Observation of body color by binocularmicroscope included overall body color, color and form of elytra, foot color, antenna and rostrum.Body sizes were measured by using ruler or millimeter scale paper by means of insect anesthesia byusing ethyl acetate, then stretching the body of insects in full on white paper with millimeter scaleplaced underneath the insects. Results of the study indicated that the S. oryzae imago were brightblack or brownish black, having four oval pictures on elytra, and reddish brown legs. Imago of S.zeamais were solid black or dark color with four yellowish brown pictures on elytra, and brownishyellow legs. The average body length of S. oryzae young adult was 2.16 mm (ranged from 2.0 to2.4 mm), and for adult was 3.36 mm (ranged from 3.0 to 3.7 mm). The average body length of S.zeamais young imago was 2.54 mm (ranged from 2.4-2.7 mm), and 4.78 mm (range 3.7 to 4.7 mm)for the older imago. The observation of adult male and female body size differences of S. oryzaeand S. zeamais showed that adult females were larger than males. The roustrum (snout) of femaleinsects was longer and bigger, while the male imago was shorter and thinner. Abdominal end of themale imago when viewed from the lateral direction showed a curved shape and when viewed fromthe posterior direction showeda tapered shape. The female abdomen when viewed from the lateraldirection was not curved or straight back, and seen from the posterior direction was rather enlargedand blunt. The average length of S. oryzaerostrum was of 0.16 mm (ranged from 0.1 to 0.24 mm)for adult males and 0.32 mm (range 0.2-0.4 mm) for adult females, while S. zeamais was 0.5 mm(ranged from 0.4-0.6 mm) formale imago, and 0.62 mm (range 0.5-0.7 mm) for female imago.Antenna of S. oryzae and S. zeamaisshowed of an angle shape with a club type. The averageantenna length ofS. oryzae was 0.94 mm (ranged from 0.8 to 1.1 mm) for adult males and 1.46 mm(range 1.2 to 1.8 mm) for adult females;S. zeamais antenna length was 1.9 mm (range 1.7- 2.1 mm)for adult males, and 2.5 mm (ranged from2.2-2.6 mm) for adult females. The sex ratio difference ofS. oryzae and S. zeamais was 0.8 (ranged from 0.7-0.9) for S. oryzae, and 0.7 (ranged from 0.67 to0.85) for S. zeamais.Key word : Characteristics of adult. S. oryzae, S. zeamais, Race, Corn.